Labor cost pass-through to producer prices in Denmark - Simon Juul Hviid; Tobias Renkin (Danmarks Nationalbank, 2020)
We estimate the pass-through of a cost-push wage shock to producer prices of firms in Denmark. We deal with the endogeneity of wages by using an identification strategy based on variation in the estimated outside option of workers within an industry. Our results suggest that the pass-through elasticity of wage increases to prices amounts to about one third when keeping the marginal product of labor constant. Our results are in line with previous studies of earlier time periods and confirm an important causal relationship between wages and prices.
Keywords: D24; E52; L11; 330; Wage pass-through; Phillips curve; Producer prices